The relationships between multimorbidity, depressive symptoms, health service utilization, and activities of daily living among the elderly in China - Lingqian Bao; Wenyun Zhang; Yudie Zhang; Min Wang; Ying Chen; Xiao Shan; Yubo Xing (PLoS ONE, 2025)
Objective This study aimed to examine the relationships between multimorbidity, depressive symptoms, health service utilization (HSU), and activities of daily living (ADL) among elderly Chinese individuals using nationally representative data. It also explored the mediating roles of depressive symptoms and HSU in the association between multimorbidity and ADL impairment, to inform strategies for improving ADL function and quality of life among the elderly. Methods The study utilized data from the 2020 wave of the China Health and Retirement Longitudinal Study (CHARLS), including 10,631 individuals aged 60 and above. A binary logistic regression model was applied to identify risk factors associated with ADL impairment in this population. Additionally, the mediating effects of depressive symptoms and HSU on the link between multimorbidity and ADL impairment were assessed using the Bootstrap method. Results In 2020, 66.2% of elderly Chinese reported multimorbidity, 43.1% experienced depressive symptoms, and 30.0% had ADL impairment. Binary logistic regression identified advanced age, female gender, recent hospitalization, multimorbidity, and depressive symptoms as independent risk factors for ADL impairment, while higher education, better self-rated health, and health insurance coverage served as protective factors. Mediation analysis showed that depressive symptoms and HSU partially mediated the link between multimorbidity and ADL impairment, accounting for 39.64% (depressive symptoms), 2.98% (outpatient visits), and 11.79% (hospitalization) of the total effect. Conclusions This study found that multimorbidity, depressive symptoms, and HSU significantly influence ADL function among elderly Chinese adults, with depressive symptoms showing a strong mediating effect. The findings highlight the need to manage multimorbidity, address mental health, and optimize healthcare use to enhance geriatric care and quality of life.